The prevalence, clinical characteristics, and brain MRI changes in intracranial artery hypoplasia: a retrospective single-center cross-sectional study - Usman, Fritz S.; Pariama, Ganda; Aiko, Novia; Kurnia, Leny; Murdianto, Harris; Kastilong, Merlin P. (International Journal of Research in Medical Sciences, 2023)
reduced cerebral blood flow, increased atherosclerosis, and aneurysm formation. This study aimed to describe the profile of vertebral artery hypoplasia (VAH), anterior CAH (ACAH), and posterior CAH (PCAH) in symptomatic subjects. Methods: This was a retrospective cross-sectional study using medical record in a secondary private hospital in Jakarta, Indonesia, in January-December 2022. The inclusion criteria were age ≥18 years with neurological symptoms, underwent brain MRI, and being diagnosed with CAH using DSA. The exclusion criteria were findings of other vascular pathologies including dissection and >50% intracranial vessel stenosis. Demographics of age, sex, body mass index (BMI), hypertension, diabetes, cardiac disorder, and previous stroke were analyzed among VAH, PCAH, and ACAH groups. Results: Of 769 subjects with clinical symptoms undergoing DSA, there were 66 (8.6%) cases of intracranial artery hypoplasia, including VAH (4.6%), PCAH (1.2%), and ACAH (2.9%). Subjects were predominantly old (53.2±10.1 years), male (53.0%), with BMI of 24.9±3.9 kg/m2 and hypertension (69.7%). Previous stroke (69.7%) was more prevalent than in previous study (28.1%). Stroke and brain ischemic lesion were detected in 89.4% and 84.8% cases. No differences were found in all parameters among all groups, but posterior circulation symptoms tended to be found in VAH (28.1%) than general stroke (20.3%). Conclusions: The high percentage of recurrent stroke and corresponding clinical symptoms associated with CAH supported that CAH may be a risk factor for clinical symptoms, including stroke, regardless of the involved artery.